Ancient and continuing Darwinian selection on insulin-like growth factor II in placental fishes - O'Neill, Michael J; Lawton, Betty R; Mateos, Mariana; Carone, Dawn M; Ferreri, Gianni C; Hrbek, Tomas; Meredith, Robert W; Reznick, David N; O'Neill, Rachel J (Proceedings of the National Academy of Sciences - PNAS, 2007)
Despite abundant examples of both adaptation at the level of phenotype and Darwinian selection at the level of genes, correlations between these two processes are notoriously difficult to identify. Positive Darwinian selection on genes is most easily discerned in cases of genetic conflict, when antagonistic evolutionary processes such as a Red Queen race drive the rate of nonsynonymous substitution above the neutral mutation rate. Genomic imprinting in mammals is thought to be the product of antagonistic evolution coincident with evolution of the placenta, but imprinted loci lack evidence of positive selection likely because of the ancient origin of viviparity in mammals. To determine whether genetic conflict is a general feature of adaptation to placental reproduction, we performed comparative evolutionary analyses of the insulin-like growth factor II (IGF2) gene in teleost fishes. Our analysis included several members of the order Cyprinodontiformes, in which livebearing and placentation have evolved several times independently. We found that IGF2 is subject to positive Darwinian selection coincident with the evolution of placentation in fishes, with particularly strong selection among lineages that have evolved placentation recently. Positive selection is also detected along ancient lineages of placental livebearing fishes, suggesting that selection on IGF2 function is ongoing in placental species. Our observations provide a rare example of natural selection acting in synchrony at the phenotypic and molecular level. These results also constitute the first direct evidence of parent-offspring conflict driving gene evolution.